Hidden healers: the unexpected ways women in prison help each other survive - Covington, Stephanie (Wiley, 2024)
"With unflinching clarity, Hidden Healers cuts through the myths about incarcerated women to expose the all-too-real brutalities they face within a criminal legal system never designed for them. Backed by three decades of experience providing therapeutic programs inside prisons across the United States, trauma specialist Dr. Stephanie S. Covington has used her unique access to amplify the voices of the women themselves. Stories from two dozen interviews with formerly incarcerated women are threaded throughout this journey into the criminal legal system, and their insights ground Covington's analysis. Hidden Healers illuminates realities most never see: that the majority who get caught up in the criminal justice system have themselves been victims of harm, that the degradations of today's prisons and jails only magnify their trauma--and that incarcerated women regularly risk punishment to tend to one another's well-being in unexpected acts of kindness. Grounded in current research and rich with personal narrative, Hidden Healers is a poignant and riveting look inside women's prisons and jails--and what we can do to help"--